RELEVANSI PENDEKATAN KLARIFIKASI ATAU TAFSIR NILAI DALAM PENGUATAN PEMBELAJARAN IPS TERPADU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Integrated Social Studies (IPS) learning is not only aimed at developing students’ conceptual knowledge but also at instilling social, moral, and civic values relevant to social life. However, in practice, IPS instruction often focuses predominantly on cognitive aspects and provides limited opportunities for students to understand, interpret, and internalize values in a reflective manner. This article aims to examine the relevance of the value clarification/interpretation approach in strengthening Integrated Social Studies learning. This study employs a qualitative approach using a literature review method by analyzing textbooks, journal articles, and previous research related to the Value Clarification Technique (VCT) in Social Studies instruction. The findings indicate that the value clarification/interpretation approach is highly relevant to be implemented in Integrated Social Studies learning, as it encourages students to think critically, reflectively, and dialogically in understanding social values. Furthermore, this approach contributes to strengthening attitudes, moral decision-making skills, and the development of students’ social character.